The influence of environmental factors on ecological beliefs and ecological behaviour of energy-efficient appliance purchase - Sai-Keong Chan; Farzana Quoquab; Rohaida Basiruddin (Asian Academy of Management Journal, 2023)
Previous ecological behaviour studies have focused on personal factors only, and thus ignored the impact of environmental factors on ecological behaviour. In addition, there are criticism on the complexity of belief component in the value-belief-norm theory. Hence, this study aims to investigate the effect of environmental factors and to assess the mediating role of ecological beliefs on energy-efficient appliance purchasing. This study utilised a questionnaire survey among 592 Malaysian consumers. The partial least squares technique was utilised to analyse the data and to test the study hypotheses. The findings show that environmental factors have a positive influence on both ecological beliefs and ecological behaviour; ecological beliefs are positively related to ecological behaviour. Additionally, ecological beliefs mediate the relationship between environmental factors and ecological behaviour. This holistic research framework helps to elaborate on the existing knowledge of environmental factors and an individual’s belief, in the context of energy-efficient appliance purchase.